Hubungan Konsumsi Makanan Sumber Zat Besi (Fe) dan Vitamin B12 terhadap Anemia Remaja Putri di Kecamatan Tuban - Mazida Nafila Deya R; Lilia Faridatul Fauziah (Lembaga Pengembangan Kinerja Dosen, 2026)
Anemia among adolescent girls remains a significant nutritional problem that affects health status, learning ability, and future productivity. One of the main contributing factors is inadequate intake of iron and vitamin B12, which are essential for hemoglobin formation. This study aimed to analyze the relationship between the consumption of iron- and vitamin B12-rich foods and the incidence of anemia among adolescent girls in Tuban District. This study employed a non-experimental design with a correlational analytic approach using a cross-sectional method. A total of 325 adolescent girls were selected using probability sampling with cluster random sampling. Data on iron and vitamin B12 intake were collected using a Semi Food Frequency Questionnaire (FFQ), while anemia status was assessed through hemoglobin levels. Data were analyzed using the Spearman Rank test with a significance level of α ≤ 0.05. The results showed that 68% of respondents were not anemic, while 32% were anemic. There was a significant relationship between iron intake and anemia (p=0.000; r=0.563) and between vitamin B12 intake and anemia (p=0.000; r=0.384), both indicating moderate correlation strength. In conclusion, iron and vitamin B12 consumption are significantly associated with anemia among adolescent girls. Higher intake of these nutrients is linked to a lower risk of anemia. These findings highlight the importance of nutrition education and balanced dietary practices in preventing anemia among adolescent girls.